Problem ochrony dzieci od wypadków przy pracy w rolnictwie - Puślecki, Damian (Wydawnictwo Naukowe UAM, 2009)
The aim of the paper is to answer the question on the level of protection rural children are given by the légal régulation on accident insurance at agricultural work. Considérations carried out in the paper form a critical assessment of current solutions, because the law on social insurance o f farmers does not extend the insurance protection to youngest persons working in agriculture, even when applying for it. The author concludes by stating that due to the family character of agricultural holdings, the specifics of agricultural work and the common practice of children helping at agricultural work there exists a need for an extension of the personal catalogue in agricultural accident insurance. The arguments given in the paper call for such an extension being committed towards children. However, this shall not be done by lowering the age of household member. Children until the age of sixteen should be specifically protected due to the burden of work given to and carried out by them.

L’articolo cerca di comprendere in quale misura la disciplina dell’assicurazione tuteli i bambini dagli infortuni sul lavoro in agricoltura. Considerazioni critiche vengono mosse alle vigenti soluzioni legislative poiché la legge sulla previdenza sociale degli agricoltori non prevede - neppure a richiesta - la copertura assicurativa per i piu giovani che effettivamente lavorano in agricoltura. In conclusione l’autore constata che, a causa del carattere familiare delle aziende agricole, della specificitá del lavoro in agricoltura e per il fatto che spesso i bambini aiutano nei lavori agricoli, esiste la necessitá di estendere dal punto di vista soggettivo l’assicurazione agricola contro gli infortuni. Gli argomenti addotti in mérito determinano la necessitá dell’estensione della tutela assicurativa a questo gruppo di persone. Ció non dovrebbe avvenire attraverso l’abbassamento dell’etá del familiare. I bambini al compimento dei 16 anni dovrebbero essere coperti di una tutela aggiuntiva dato l’entitá dei lavori eifettuati.
Child protection against accidents at agriculture work
La tutela dei bambini dagli infortuni sul lavoro in agricoltura